2015
DOI: 10.1785/0120140259
|View full text |Cite
|
Sign up to set email alerts
|

Separation of Intrinsic and Scattering Attenuation Using Single Event Source in South Korea

Abstract: Simultaneous use of numerous events in the multiple lapse time window analysis (MLTWA) method is the most effective way to obtain Q −1 i and Q −1 S values. Such simultaneous use of numerous events normally shows a large observational scatter, which may be caused by different radiation pattern and focal depth of each earthquake, and regional alteration of the local structure. To avoid these scattering factors, the current study attempted to use single event source as the input data in MLTWA for South Korea. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 53 publications
(48 reference statements)
0
13
0
Order By: Relevance
“…The change in Qc as the depth increases, in other words as the lapse time increases has become a subject which many researchers have become interested in.Such studies are numerous especially inactive tectonic areas. In the studies when the lapse timeis 20 sec., [9] calculated Qc = 29f 0.9 in their study at Etna and Granada, [12] calculated Qc = 64f 0.9 in their study at volcanic area in the southeastern area of Sicily, [13] calculated Qc = 66f 1.16 in the Koyna area, and in the studies performed with a lapse time of 20 sec., Qc = 96f 1.09 had been calculated, and in the studies performed with a lapse time 40 sec. Qc = 131f 1.04 had been calculated.…”
Section: Resultsmentioning
confidence: 99%
“…The change in Qc as the depth increases, in other words as the lapse time increases has become a subject which many researchers have become interested in.Such studies are numerous especially inactive tectonic areas. In the studies when the lapse timeis 20 sec., [9] calculated Qc = 29f 0.9 in their study at Etna and Granada, [12] calculated Qc = 64f 0.9 in their study at volcanic area in the southeastern area of Sicily, [13] calculated Qc = 66f 1.16 in the Koyna area, and in the studies performed with a lapse time of 20 sec., Qc = 96f 1.09 had been calculated, and in the studies performed with a lapse time 40 sec. Qc = 131f 1.04 had been calculated.…”
Section: Resultsmentioning
confidence: 99%
“…Interpretation of the coda Q results in terms of scattering and intrinsic Q is not an exact science, as evidenced by the many often conflicting proposals (e.g., Frankel and Wennerberg, 1987;Bianco et al, 2002;Carcole and Sato, 2010;Rachman et al, 2015) and is out of scope for this study. We will also not try to compare coda Q estimates from our study with studies using other methods.…”
Section: Introductionmentioning
confidence: 97%
“…(mainly western Europe) are marked by blue diamonds (Lacombe et al, 2003;Sens-Schönfelder & Wegler, 2006;Sens-Schönfelder et al, 2009) and volcanoes by red diamonds (Mayeda et al, 1992;Del Pezzo et al, 2001;Wegler, 2003;Ugalde et al, 2010). Minimum and maximum values for absorption and scattering in Japan (Carcolé & Sato, 2010), Korea (Rachman et al, 2015) and North America (Eulenfeld & Wegler, 2017) are also shown.…”
Section: Comparison With Others Studiesmentioning
confidence: 99%